1987
DOI: 10.1161/01.str.18.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow in essential hypertension: data evaluation by a mapping system.

Abstract: Regional cerebral blood flow was studied by means of the U3 Xe inhalation method hi 26 untreated and 10 treated patients with essential hypertension. The untreated subjects were divided into newly and previously diagnosed groups to assess the relation between regional cerebral blood flow and the duration of hypertension. The overall flow reduction was more marked in the frontal and temporal regions hi the previously diagnosed group, and this was attributed to pathological changes in the district served by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…This suggests that perforating arteries are not sufficiently supplied with nutritional elements or oxygen, which can only be obtained from the arterial lumen. It was previously confirmed that regional cerebral flow decreased in stroke-prone SHR (24), as well as in humans, with the development of hypertension (13). Our results, obtained through stroke-prone SHR and stroke victims, suggest that deficiency of nutrients and oxygen may be the cause of the medial necrosis.…”
Section: Discussionsupporting
confidence: 84%
“…This suggests that perforating arteries are not sufficiently supplied with nutritional elements or oxygen, which can only be obtained from the arterial lumen. It was previously confirmed that regional cerebral flow decreased in stroke-prone SHR (24), as well as in humans, with the development of hypertension (13). Our results, obtained through stroke-prone SHR and stroke victims, suggest that deficiency of nutrients and oxygen may be the cause of the medial necrosis.…”
Section: Discussionsupporting
confidence: 84%
“…12 However, the xenon-133 inhalation method reveals a significant inverse relation between MABP and mean hemispheric CBF. 3 Hypertension has been shown to be an important risk factor for reduced CBF among neurologically normal volunteers 10 and among patients with transient ischemic attacks. 11 An autopsy study in Hisayama, Japan, 12 has shown that cerebral atherosclerosis occurs 20-30 years earlier in hypertensive than in normotensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 -2 Using the xenon-133 inhalation method, Rodriguez et al 3 recently demonstrated a significant inverse correlation between mean arterial blood pressure (MABP) and mean hemispheric CBF. Structural adaptation of the vascular wall to longstanding hypertension, such as hypertrophy of smooth muscle and proliferation of connective tissue, 4 -5 may play an important role in reducing CBF by encroaching on the arterial lumen.…”
Section: Erebral Blood Flow (Cbf) In Hypertensivementioning
confidence: 99%
“…A significant inverse correlation between CBF and MAP has also been reported in hypertensive patients. For example, CBF measured by 133Xe inhalation technique was higher in hypertensive patients who were receiving antihypertensive agents than in those with newly diagnosed, non-treated hypertension (14). The appopriate treatment of hypertension, the longer the better, may therefore possibly improve cerebral hypoperfusion in hypertensive patients.…”
Section: Cerebral Blood Flowmentioning
confidence: 99%